A study on antibacterial, antioxidant, and hepatoprotective efficacy of Elephantopus scaber L. - Phuc, Nguyen Trong Hong; Dat, Nguyen Trong Hong (Penerbit Universiti Kebangsaan Malaysia, 2022)
Elephantopus scaber is an herb widely used in folk remedies in Vietnam, especially in the treatment of liver disease. However, scientific studies evaluating the activity and ability to treat the disease in a scientific way are still very limited. This study evaluated the antibacterial, antioxidant, acute toxicity and hepatoprotective efficacy of E. scaber extracts. The extracts restricted the growth of 6 types of bacteria, being particularly most effective against E. coli. It was found that the E. scaber leaves extract was more efficient than root, stem, flower, and whole plant extracts. DPPH assay showed that the flower extract had the highest antioxidant activity (EC50 = 60.29 μg/mL). The E. scaber extracts (>5000 mg/kg) also did not cause acute toxicity in mice. Additionally, the extracts effectively protected and recovered mice liver cells damaged by CCl4. The reduction of mice liver enzyme levels (AST and ALT) was similar between the extracts and silymarin. This hepatoprotective efficiency was also illustrated by the morphology and histology of the mice liver cells. The extracts healed mice liver cells by recovering the cell diameter, reducing inflammation swelling and increasing Hb concentration.